Identification and notification of situations of violence in Primary Health Care: the permanent education as a tool for professional qualification (Research, Society and Development, 2022)
This is an intervention research with a qualitative approach, on the development of a cycle of Continuing Education in Health, carried out with professionals working in a Family Health Center (FHC) of a city in the countryside of Ceará. The intervention aimed to qualify the professionals' performance regarding the identification and notification of domestic violence situations in Primary Health Care (PHC). It is noted some obstacles that cross the field of professional practices, specifically regarding the lack of understanding and association between notification and denunciation, as well as the feeling of unpreparedness on the part of some professionals, for the management and care of this type of demand. We suggest the necessity and constancy of moments of permanent education in order to qualify and sensitize the professional practices, since the integral care presupposes a holistic view of the subjects, thus ensuring the care of their needs beyond the physical field.